2015
DOI: 10.1128/jvi.02620-14
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasomal Rpn11 Metalloprotease Suppresses Tombusvirus RNA Recombination and Promotes Viral Replication via Facilitating Assembly of the Viral Replicase Complex

Abstract: RNA viruses co-opt a large number of cellular proteins that affect virus replication and, in some cases, viral genetic recombination. RNA recombination helps viruses in an evolutionary arms race with the host's antiviral responses and adaptation of viruses to new hosts. Tombusviruses and a yeast model host are used to identify cellular factors affecting RNA virus replication and RNA recombination. In this study, we have examined the role of the conserved Rpn11p metalloprotease subunit of the proteasome, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 70 publications
(129 reference statements)
1
25
0
Order By: Relevance
“…Normally, Rpn11p functions to couple de-ubiquitination of substrates with proteasomal degradation, and also contributes to tombusvirus replication [31,38,39]. Rpn11p gained the attention of researchers working on TBSV replication because it was initially identified to function in peroxisome division, and TBSV replication occurs inside spherules along peroxisomal membranes.…”
Section: Ubiquitin Proteasome System Supporting Virus Replication mentioning
confidence: 99%
“…Normally, Rpn11p functions to couple de-ubiquitination of substrates with proteasomal degradation, and also contributes to tombusvirus replication [31,38,39]. Rpn11p gained the attention of researchers working on TBSV replication because it was initially identified to function in peroxisome division, and TBSV replication occurs inside spherules along peroxisomal membranes.…”
Section: Ubiquitin Proteasome System Supporting Virus Replication mentioning
confidence: 99%
“…The Nedd4-type Rsp5p E3 Ub-ligase has also been shown to bind to and ubiquitinylate p33 replication protein in vitro (Barajas et al, 2009b). Studies with the proteasomal Rpn11p metalloprotease, which acts as a deubiquitination (DUB) enzyme, has shown the role of Rpn11p in the assembly of TBSV VRCs, and the recruitment of the cellular DDX3-like Ded1p DEAD-box helicase into the viral replicase (Prasanth et al, 2014). Data also support the role of Rpn11p and the free ubiquitin pool in TBSV replication and viral RNA recombination (Prasanth et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Studies with the proteasomal Rpn11p metalloprotease, which acts as a deubiquitination (DUB) enzyme, has shown the role of Rpn11p in the assembly of TBSV VRCs, and the recruitment of the cellular DDX3-like Ded1p DEAD-box helicase into the viral replicase (Prasanth et al, 2014). Data also support the role of Rpn11p and the free ubiquitin pool in TBSV replication and viral RNA recombination (Prasanth et al, 2014). Altogether, the emerging idea from these studies on TBSV that ubiquitin and protein ubiquitination is a major element in virus replication and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple genome-wide screens with TBSV in yeast indicated that depletion of a proviral host factor does not necessarily prevent the assembly of the VRCs (4) but frequently leads to incorrect VRC assembly that changes some of the activities of the viral replicase. For example, depletion of multifunctional proteasomal Rpn11p metalloprotease in yeast results in inefficient recruitment of Ded1p DEAD box helicase into the tombusvirus VRCs (14). The low level of Ded1p leads to reduced replication and the production of high levels of truncated viral RNAs and recombinant viral RNAs (14).…”
mentioning
confidence: 99%
“…For example, depletion of multifunctional proteasomal Rpn11p metalloprotease in yeast results in inefficient recruitment of Ded1p DEAD box helicase into the tombusvirus VRCs (14). The low level of Ded1p leads to reduced replication and the production of high levels of truncated viral RNAs and recombinant viral RNAs (14). Also, depletion of ESCRT proteins (Vps24 or Vps4p) results in incorrect assembly of tombusvirus VRCs in yeast, which gives rise to spherules with wide openings, instead of the narrow "neck-like" opening in wild-type (wt) yeast (8).…”
mentioning
confidence: 99%